Behavioral and technology implications of electromobility on household travel emissions. (May 2021) - Srinivasa Raghavan, Seshadri; Tal, Gil
Highlights: Benefits of BEVs are predicated upon household preferences and vehicle attributes. Operationalization of UF gains may complement or offset GHG reduction benefits. Longer-range efficient BEVs are better for reducing household travel emissions. Longer-range sportier performance BEVs improves the UF. Driving a fully charged BEV instead of ICE whenever feasible saves 90–150 GGEq/year. Abstract: This paper investigates the share of household travel electrified or Utility Factor(UF) and well-to-wheel(WtW) greenhouse gas(GHG) emissions of battery electric vehicles(BEVs) in two-car households. We examine a multiyear travel data collected via GPS loggers from both vehicles(internal combustion engine vehicle-ICE and BEV) belonging to 73 California households:30 Nissan Leaf, 21 Chevy Bolt, and 22 Tesla ModelS. Results indicate that two distinct substitution patterns moderated by vehicle attributes effectuate diversified outcomes on UF and GHG. Energy efficiency losses due to technology and user preferences counteracts range enabled UF gains offsetting BEV's GHG benefits. Fuel inefficient ICEs could aggravate emissions of longer-range BEV households. Conversely, energy efficiency improvements can augment GHG reduction, but UF decreases. Maximum UF of 75–80% can be achieved by upgrading to a longer-range BEV. Longer-range performance-oriented BEV upgrade does not improve UF but nullifies 15–30% of emission abatement potential realized by driving their existing BEV instead of ICE.